Electricity Concepts’ Test Construction, Validation, and Item Analysis for Senior High School General Physics 2 - Carolino, Lloyd Ian E; Cacho, Rubylen M.; Batalla, Beverly D.; Manaois, Adrian R.; Melendez, Joshua B.; Sison, Maricris M.; Gagujas, Melissa B.; Camara, Jun S. (Southeast Asian Journal of Science and Technology, 2021)
This study aimed to design (i.e. develop and validate) a test material for selected topics in Electricity in the context of Philippine Senior High School’s General Physics 2. The draft test package underwent careful test construction, content-validation of faculty-experts, readability test for reading ease, pilot-testing with item analysis using Henning’s and Ebel’s scales. The test package was pilot tested among STEM students in a public national high school in Pangasinan, Philippines with a participation rate of 76.67%. Findings reported the increasing item retention rate of the following: Eletric Fields (70.00%) > Coulomb’s Law (71.43%) > Electric Charge (75.00%) > Electric Potential (83.33%) > Electric Flux (100.00%). The low number of item revision could be attributed to the careful planning of the researchers, as well as substantive feedbacks of the faculty-experts as content validators. Implications on the fitness of the test material for Pangasinan context is manifested because of the huge item retention rate, while recommendation for its use necessitates further revalidation. Distracter analysis on items retained is recommended. Finally, the institutionalization for his OBE strategy in the teaching of Assessment in Learning 1 is hereby recommended as well.